RELATIVE GROWTHS OF BODY PARTS AND LENGTH-WEIGHT RELATIONSHIPS IN BOLEOPHTHALMUS DUSSUMIERI AND B. DEN TAWS OF KARACHI COAST - Hoda, S M Shamsul (Indian Journal of Fisheries, 2011)
Different morphometric characters of Bolcophthalmus dussumieri Ciiv. &. Val. and B. dentatus Cuv. & Val. collected from the Karachi coast between April and December 1982 showed linear relationships. The fastest growing part in both the species is the preanal, followed by predorsal and caudal fin, and the slowest growing part is the eye-diameter, followed by snout. Separate equations for describing the length-weight relationships for males and females are justified. The males and females do not follow ’cube law’. The Relative condition factor reveals that maturation starts from 60-65 mm SL onwards in males and 70-75 mm SL onv/ards in females in both the species